Is "pre-sepsis" the new sepsis? A narrative review. - Rémy Gerard; Antoine Dewitte; Fridolin Gross; Thomas Pradeu; Maël Lemoine; Julien Goret; Maria Mamani-Matsuda (PLoS Pathogens)
Sepsis is a life-threatening condition caused by a dysregulated immune response to infection, leading to organ dysfunction and high mortality. Despite advances in treatment, sepsis remains difficult to manage. Historically, the concept of sepsis evolved from ancient observations of infection-related decay to the germ theory of the 19th century. The latest Sepsis-3 definition describes sepsis as life-threatening organ dysfunction due to a dysregulated host response. However, this clinical characterization may be too late for effective intervention. The concept of endotypes and the ontological data applied to sepsis highlight the substantial heterogeneity in pathophysiological pathways leading to this endpoint. We propose a focus on the "pre-sepsis" phase, where early immune dysregulation arises before significant organ damage. This phase represents the host's initial response to infection, preceding sepsis and, thus, organ failure. Currently, there is no formal definition of "pre-sepsis", but this phase could be defined on the basis of early biological pathways in host-pathogen interactions, such as those involving endogenous carbon monoxide. By focusing on "pre-sepsis" and developing tools to detect it, clinicians could intervene earlier and potentially prevent the progression to sepsis. This approach may lead to improved outcomes and more personalized treatments, targeting specific immune pathways tailored to patient profiles. Ultimately, this shift could address existing challenges in sepsis treatment, offering new directions for clinical research and therapeutic development.